New Structures Based on the Mixed Valence Polyoxometalate Cluster [V 12b18o60h6]N- - Costamagna-Martra, J; Costamagna-Martra, J; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (2012)
Sin Editorial Disponible